Antileishmanial effect and immunomodulatory activity of Tinospora cordifolia and Withania somnifera against experimental BALB/c mice (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
Visceral leishmaniasis (VL) is a vector-borne disease that progress mainly by lowering of immune protective cells Th1 and the appearance of cells Th2 that promote illness therefore the treatment of this disease relies on improving the immune condition of the host. Currently used treatment options of VL are Amphotericin B (AmB) and its liposomal formulation i.e., Ambisome. But these treatment options are not safe as these drugs have many side effects and limitations like hepatotoxicity, nephrotoxicity, VL relapse and PKDL conversion. This has prompted the search for alternative treatment options amongst herbal drugs; Thus, This study investigated Tinospora cordifolia and Withania somnifera's antileishmanial potentia, either in combination or alone. In vivo experiments demonstrated a substantial decrease in BALB/c mice in the spleen parasitic burden. Moreover, the treatment effectively modulated immune response of the host, leading to Th1 polarization, crucial for eliminating Leishmania donovani. This method not only targets the parasite but also fortifies the immune system, offering a safer, cost-effective alternative to current therapies for Visceral leishmaniasis, which are often limited by toxicity and resistance.